The Atlantic Coast Conference (ACC) Website (2008)
The Atlantic Coast Conference, through its member institutions, seeks to maximize the educational and athletic opportunities of its student-athletes, while enriching their quality of life. It strives to do so by affording individuals equitable opportunity to pursue academic excellence and compete at the highest level of intercollegiate athletics competition in a broad spectrum of sports and championships. The Conference will provide leadership in attaining these goals, by promoting diversity and mutual trust among its member institutions, in a spirit of fairness for all. It strongly adheres to the principles of integrity and sportsmanship, and supports the total development of the student-athlete and each member institution's athletics staff, with the intent of producing enlightened leadership for tomorrow. The Atlantic Coast Conference was founded on May 8, 1953, at the Sedgefield Inn near Greensboro, N.C., with seven charter members - Clemson, Duke, Maryland, North Carolina, North Carolina State, South Carolina and Wake Forest - drawing up the conference by-laws.